A comparison of tracheal scaffold strategies for pediatric transplantation in a rabbit model. (4th August 2017) - Maughan, Elizabeth F.; Butler, Colin R.; Crowley, Claire; Teoh, Gui Zhen; Hondt, Margot Den; Hamilton, Nicholas J.; Hynds, Robert E.; Lange, Peggy; Ansari, Tahera; Urbani, Luca; Janes, Samuel M.; Coppi, Paolo De; et al.
Abstract : Objectives/Hypothesis: Despite surgical advances, childhood tracheal stenosis is associated with high morbidity and mortality. Various tracheal scaffold strategies have been developed as the basis for bioengineered substitutes, but there is no consensus on which may be superior in vivo. We hypothesized that there would be no difference in morbidity and mortality between three competing scaffold strategies in rabbits. Study Design: Pilot preclinical study. Methods: Tracheal scaffolds were prepared by three methods that have been applied clinically and reported: preserved cadaveric ("Herberhold") allografts, detergent‐enzymatically decellularized allografts, and synthetic scaffolds (nanocomposite polymer [polyhedral oligomeric silsesquioxane poly(carbonate‐urea) urethane (POSS‐PCU)]). Scaffolds were implanted into cervical trachea of New Zealand White rabbits (n = 4 per group) without cell seeding. Control animals (n = 4) received autotransplanted tracheal segments using the same technique. Animals underwent bronchoscopic monitoring of the grafts for 30 days. Macroscopic evaluation of tissue integration, graft stenosis, and collapsibility and histological examinations were performed on explants at termination. Results: All surgical controls survived to termination without airway compromise. Mild to moderate anastomotic stenosis from granulation tissue was detected, but there was evidence suggestive of vascular reconnection with minimal fibrous encapsulation. In contrast, three of the four animals in the Herberhold and POSS‐PCU groups, and all animals receiving decellularized allografts, required early termination due to respiratory distress. Herberhold grafts showed intense inflammatory reactions, anastomotic stenoses, and mucus plugging. Synthetic graft integration and vascularization were poor, whereas decellularized grafts demonstrated malacia and collapse but had features suggestive of vascular connection or revascularization. Conclusions: There are mirror‐image benefits and drawbacks to nonrecellularized, decellularized, and synthetic grafts, such that none emerged as the preferred option. Results from prevascularized and/or cell‐seeded grafts (as applied clinically) may elucidate clearer advantages of one scaffold type over another. Level of Evidence: NA. Laryngoscope, 127:E449–E457, 2017